FEMINISM IN INDONESIA AND THE PERSPECTIVE OF THE MOHANTY’S “THIRD WORLD FEMINISM” - Galuh Dwi Ajeng (English Department, STKIP PGRI Bandar Lampung, 2021)
This research article presents the study about the analysis of feminism in Indonesia associated with the perspective of the term third world feminism in Chandra Talpade Mohanty’s essay. The condition of Indonesian feminism movement is analysed by considering the book of R.A. Kartini, meanwhile the third world feminism is analysed by considering the content of Mohanty’s essay. This study employs qualitative research method. In her essay, Mohanty explores the idea of the third world feminism that has been issued by the western feminists. The terms of first world feminism, third world feminism as well as the ethnocentric have been differentiated by them. The finding of this study shows that feminism in Indonesia has a long history and has contributed to the discourse of equality as a critical project that brings social change. The feminism movements in Indonesia have already created the emancipation awareness among the people. This feminism movements have provided a proof that it needs to avoid the same generalization of the condition of feminism among the non-western countries.